An alternative method for investigating the effect of squeezing flow of a Casson fluid between parallel walls on magnetic field. (2022) - Alao, Saheed; Oderinu, Rasaq Adekola; Akinola, Emmanuel Idowu; Opaleye, Olusola Emmanuel
No abstract available